Cryoloading: introducing large molecules into live synaptosomes - Nath, Arup R.; Chen, Robert H.; Stanley, Elise F. (Frontiers in Cellular Neuroscience, 2014)
Neurons communicate with their target cells primarily by the release of chemical transmitters from presynaptic nerve terminals. The study of CNS presynaptic nerve terminals, isolated as synaptosomes (SSMs) has, however, been hampered by the typical small size of these structures that precludes the introduction of non-membrane permeable test substances such as peptides and drugs. We have developed a method to introduce large alien compounds of at least 150 kDa into functional synaptosomes. Purified synaptosomes are frozen in cryo-preserving buffer containing the alien compound. Upon defrosting, many of the SSMs contain the alien compound presumably admitted by bulk buffer-transfer through the surface membranes that crack and reseal during the freeze/thaw cycle. ~80% of the cryoloaded synaptosomes were functional and recycled synaptic vesicles (SVs), as assessed by a standard styryl dye uptake assay. Access of the cryoloaded compound into the cytoplasm and biological activity were confirmed by block of depolarization-induced SV recycling with membrane-impermeant BAPTA (a rapid Ca2+-scavenger), or botulinum A light chain (which cleaves the snare protein SNAP25). A major advantage of the method is that loaded frozen synaptosomes can be stored virtually indefinitely for later experimentation. We also demonstrate that individual synaptosome types can be identified by immunostaining of receptors associated with its scab of attached postsynaptic membrane. Thus, cryoloading and scab-staining permits the examination of synaptic vesicle recycling in identified individual CNS presynaptic nerve terminals.